Peptide chemistry and drug design - Dunn, Ben M. (New Jersey : John Wiley & Son, Inc., 2015)
This book details many of the problems and successes of peptides as potential drugs.
Peptide therapeutics -- Methods for the peptide synthesis and analysis -- Peptide design strategies for g-protein coupled receptors -- Peptide-based inhibitors of enzymes -- Discovery of peptide drugs as anzyme inhibitors and activators -- Discover of peptide drugs from natural sources -- Modification of peptides to limit metabolism -- Delivery of peptide drugs
Includes bibliographical references and index.
Keywords: DRUG DESIGN; MEDICAL PHARMACOLOGY